The Impact of Private Education Sector to The Development of Bukimbiri Sub-County, Kisoro District. - Tibesigwa, David (Kabale University, 2023)
African countries embraced structural adjustment programs under the advisement of World Bank and International Monetary Fund (EMF) in order to improve access to and participate in basic education for all; improve learning outcomes and improve equity in educational opportunities The policy of privatization has been taken into all spheres of the economy which is very critical to realize elements of development and equity of the "developing nations" African Economies usually manage to only fund a half of their budgets and therefore are reliant on donor aid. The education sector is one sector that has funded by donor money but is yet to witness a major change because it is still riddled with inadequate teachers, facilitation and other challenges. This has pushed governments; Bukimbiri sub county government being of them to open up the education spectrum to the public so that the "future leaders" are provide with education services at a --cheaper price" but of primary quality hence the countries witnessing growth and development of their economies. This Study found out that level of development in Atrican education sector has increased youth innovativeness and entering the job market. Further it has improved learning outcomes and equity in educational opportunities. This has not happened in space but due to better infrastructure. political stability. political freedoms and rights, Governance and level of sciences and technology. The study found out that privatization in the education sector has not really achieved what it set out to. Rural have cited primary fees as one of the major challenges and other institutional challenges mentioned include but not limited to: limited funding. stringent government policies; primary taxation. poverty. poor infrastructural development, corruption, unrest and population explosion (where infrastructure cannot handle the numbers). In recommendations, if some of these challenges are addressed Africa may surely rise up like china and other Asian tigers that have become an education destination. Keywords: Impact, Private Education Sector, Development, Bukimbiri Sub-County, Kisoro District.